Distribution and current problems of acute endovascular therapy for large artery occlusion from a two-year national survey in Japan. Issue 3 (April 2020) - Takagi, Toshinori; Yoshimura, Shinichi; Sakai, Nobuyuki; Iihara, Koji; Oishi, Hidenori; Hirohata, Masaru; Matsumaru, Yuji; Matsumoto, Yasushi; Yamagami, Hiroshi; Menon, Bijoy K; Almekhlafi, Mohammed; Holodinsky, Jessalyn K; et al.
Background: Endovascular treatment is recommended in clinical practice in Japan. However, its utilization and comprehensiveness are less well described. Aims: To report endovascular treatment utilization and overall geographical coverage in Japan and to analyze regional differences in the number of endovascular treatments, specialists, and endovascular treatment-capable hospitals. Methods: A national survey of members of the Japanese Society for NeuroEndovascular Therapy (JSNET) was conducted in 2017 and 2018. The total number of endovascular treatment cases per year was estimated, and the number of endovascular treatment cases per 100, 000 people was calculated using the 2015 census. The distribution of treatment hospitals and JSNET specialists was mapped and the population coverage rate was determined. Results: The total number of endovascular treatment cases in Japan increased by 34.5% from 2016 (7702) to 2017 (10, 360). The number of endovascular treatment-capable hospitals in Japan increased from 597 in 2016 to 693 in 2017, with an average annual caseload of 14.9 in 2017. The number of JSNET specialists per hospital decreased from 1.81 in 2016 to 1.76 in 2017 because of the increase in endovascular treatment-capable hospitals. Only 50 (7.2%) hospitals had > 40 endovascular treatment cases annually. The majority (97.7%) of the Japanese population lives within a 60-min drive of any endovascular treatment-capable hospital. However, only 70.4% live within a 60-min drive of a high-volume center (>40 cases annually). Conclusions: Utilization of endovascular treatment in Japan is increasing; however, the number of cases per hospital remains low, as is the number of specialists per endovascular treatment-capable hospital. Increased number of specialists and centralization of endovascular treatment services may improve patient outcomes.